Racial Differences in Response to Trauma: Comparing African-American, White, and Hispanic People With Severe Mental Illness. Issue 2 (3rd April 2019) - O'Hare, Thomas; Shen, Ce; Sherrer, Margaret V.
ABSTRACT: Objective : To test hypotheses that Hispanics will report greater posttraumatic stress symptoms than Whites or African-Americans with severe mental illness ( N  = 132) when lifetime trauma, psychiatric symptoms, and negative appraisal of trauma are controlled; and, that negative appraisal will mediate trauma and posttraumatic stress symptoms for Hispanics. Methods : Data were collected by staff in an urban community mental health center. Results : Hispanics reported greater posttraumatic stress symptoms, and negative appraisals mediated trauma and posttraumatic stress symptoms in Hispanics only. Conclusions : Practitioners should target both the intensity and meaning of trauma and its consequences as they may vary by ethnic/racial background.